A hemicyanine-based fluorescent probe for hydrazine detection in aqueous solution and its application in real time bioimaging of hydrazine as a metabolite in mice. Issue 20 (26th April 2019) - Li, Tao; Liu, Jian; Song, Linjiang; Li, Zicheng; Qi, Qingrong; Huang, Wencai
Abstract : A fluorescent probe, Hcy-Ac, was developed for the monitoring of in situ hydrazine release during the metabolism of isoniazid. Abstract : A hemicyanine-based fluorescent probe, Hcy-Ac, was developed for the specific detection of hydrazine. With good water solubility and high sensitivity, Hcy-Ac has been successfully applied for the monitoring of in situ hydrazine release during the metabolism of isoniazid in mice.